THE INFLUENCE OF ATTITUDES AND PERCEPTIONS ON ONLINE SHOPPING INTEREST IN THE KOLAKA JUAL BELI FACEBOOK GROUP - Sari, Respita; Ismanto; Sudarnice (PT. Sangadji Media Publishing, 2024)
The aim of this research is to analyze the influence of attitudes and perceptions on online shopping interest in the Kolaka buying and selling Facebook group. This study uses a quantitative approach. The sample used was 346 respondents who were interested in online shopping in the Kolaka buying and selling Facebook group. The sampling technique used was purposive sampling, research data analysis used the Structural Equation Modeling (SEM-PLS) method. The research results show that attitude has a positive and significant effect on online shopping interest. This is proven by the t-count or t-statistic which is higher than the t-table value which is 6.370. The research results also show that perception has a positive and significant effect on online shopping interest because the t-count or t-statistic value is higher than the value t-table is 3.829. The attitudes held by each consumer can have a big influence on interest in online shopping, especially Kolaka people who make purchases in the KJB group (Kolaka Jual Beli) and consumer perceptions have an influence on online shopping interest, especially Kolaka people who make purchases in the group (Kolaka Jual Beli) KJB.